1998
DOI: 10.1103/physrevlett.81.2438
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance of Elliptic Flow: A New Probe for the Nuclear Equation of State

Abstract: Using a relativistic hadron transport model, we investigate the utility of the elliptic flow excitation function as a probe for the stiffness of nuclear matter and for the onset of a possible quark-gluon-plasma (QGP) phasetransition at AGS energies 1 < ∼ E Beam < ∼ 11 AGeV. The excitation function shows a strong dependence on the nuclear equation of state, and exhibits characteristic signatures which could signal the onset of a phase transition to the QGP.PACS 25.75.Ld, 24.85.+p, 24.10.Jv Typeset using REV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
172
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(184 citation statements)
references
References 21 publications
(23 reference statements)
9
172
3
Order By: Relevance
“…A more consistent method is perhaps to use density-or temperature-dependent quark masses, so that they correspond to current masses at high temperature and constituent masses at low temperature near the phase transition, where a scalar field is responsible for the changing masses. This method also has the advantage that it can qualitatively describe the equation of state of the QGP [182]. Also, the current coalescence model could have problems with entropy, because quark coalescence reduces the number of particles by a factor of 2 to 3, although entropy also depends on the degeneracy and mass of produced hadrons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more consistent method is perhaps to use density-or temperature-dependent quark masses, so that they correspond to current masses at high temperature and constituent masses at low temperature near the phase transition, where a scalar field is responsible for the changing masses. This method also has the advantage that it can qualitatively describe the equation of state of the QGP [182]. Also, the current coalescence model could have problems with entropy, because quark coalescence reduces the number of particles by a factor of 2 to 3, although entropy also depends on the degeneracy and mass of produced hadrons.…”
Section: Discussionmentioning
confidence: 99%
“…Elliptic flow in heavy ion collisions is a measure of the asymmetry of particle momentum distributions in the transverse plane and is generated by the anisotropic pressure gradient in initial hot dense matter as a result of the spatial asymmetry in noncentral collisions [178][179][180][181][182][183]. It is defined as one half of the second Fourier coefficient of the azimuthal angle distribution of particle transverse momentum and can be evaluated as…”
Section: H Elliptic Flowmentioning
confidence: 99%
“…The hadron transverse momentum anisotropy is generated by the pressure anisotropy in the initial compressed matter formed in noncentral heavy-ion collisions [2,3] and is sensitive to the properties of produced matter in these collisions. For heavy-ion collisions at the Relativistic Heavy Ion Collider (RHIC), it has been shown that this sensitivity exists not only in the larger elliptic flow [4][5][6][7][8][9][10][11] but also in smaller higher order anisotropic flows [12][13][14][15][16][17][18]. To investigate the influence of initial collision geometry on anisotropic flows in heavy-ion collisions, one usually varies the impact parameter of a collision or the atomic number of colliding nuclei [19].…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the eeliptic flow depends on both initial spatial asymmetry in non-central collisions and the subsequent collective interactions. The elliptic flow is thus sensitive to the properties of the dense matter formed during the initial stage of heavy ion collision [2,3,4,5] and parton dynamics [6] at Relativistic Heavy Ion Collider (RHIC) energies. Experimentally, elliptic flow has been measured as functions of collision centrality, transverse momentum, (pesudo)rapidity and particle species [7,8,9,10,11] in 197 Au + 197 Au collisions from RHIC at Brookhaven National Laboratory (BNL).…”
Section: Introductionmentioning
confidence: 99%